Inclusive leadership (Assemble You, 2022)
Welcome to Audio Learning from Assemble You. Building inclusive leadership skills is a critical component of being a great business leader and inspiring the best from individuals and teams. When you can use inclusive leadership effectively, the people in your organization thrive, products and services are elevated, and your business customers win too. In this track, we highlight the impact that inclusive leadership can have and then talk through a number of different things to look out for or be aware of as a leader. Learning Objectives Learn to go beyond ticking boxes and integrate diversity and inclusiveness into your culture Learn to identify and understand your own biases Learn to lead your people with diversity, inclusion and equality.